Diacylglycerol Kinases Are Widespread in Higher Plants and Display Inducible Gene Expression in Response to Beneficial Elements, Metal, and Metalloid Ions - Escobar-Sepúlveda, Hugo F.; Trejo-Téllez, Libia I.; Pérez-Rodríguez, Paulino; Hidalgo-Contreras, Juan V.; Gómez-Merino, Fernando C. (Frontiers in Plant Science, 2017)
Diacylglycerol kinases (DGKs) are pivotal signaling enzymes that phosphorylate diacylglycerol (DAG) to yield phosphatidic acid (PA). The biosynthesis of PA from phospholipase D (PLD) and the coupled phospholipase C (PLC)/DGK route is a crucial signaling process in eukaryotic cells. Next to PLD, the PLC/DGK pathway is the second most important generator of PA in response to biotic and abiotic stresses. In eukaryotic cells, DGK, DAG and PA are implicated in vital processes such as growth, development and responses to environmental cues. A plethora of DGK isoforms have been identified so far, making this a rather large family of enzymes in plants. Herein we performed a comprehensive phylogenetic analysis of DGK isoforms in model and crop plants in order to gain insight into the evolution of higher plant DGKs. Furthermore, we explored the expression profiling data available in public data bases concerning the regulation of plant DGK genes in response to beneficial elements and other metal and metalloid ions, including silver (Ag), aluminum (Al), arsenic (As), cadmium (Cd), chromium (Cr), mercury (Hg) and sodium (Na). In all plant genomes explored, we were able to find DGK representatives, though in different numbers. The phylogenetic analysis revealed that these enzymes fall into three major clusters, whose distribution depends on the composition of structural domains. The catalytic domain conserves the consensus sequence GXGXXG/A where ATP binds. The expression profiling data demonstrated that DGK genes are rapidly but transiently regulated in response to certain concentrations and time exposures of beneficial elements and other ions in different plant tissues analyzed, suggesting that diacylglycerol kinases may mediate signals triggered by these elements. Though this evidence is conclusive, further signaling cascades that such elements may stimulate during hormesis, involving the phophoinositide signalling pathway and diacylglycerol kinase genes and enzymes, remain to be elucidated.